Speed Control and Direction Control of Dc Motor Using Arm7 (International Journal of Engineering and Computer Science, 2015)
An armature voltage control is used to control the supplied voltage of an armature of a 2kw separately excited DC motor. A buckregulator is used to vary the supplied voltage of the motor. A pulse width modulation (PWM) generator is implemented to supplythe signal to the gate of the switch of the buck regulator. A series or cascade compensator is placed to control the duty cyclone ofthe pulse width modulation (PWM) generator in the closed loop control system. Pulse width modulation has one additionaladvantage which is that the pulse reaches the full supply voltage. It will produce more torque in a motor easily overcome motorresistance.SST 433 MHZ transmitter and STR 433MHZ receiver are the RF module used here.AT the end of the transmitter, fourswitches are provided to control the speed and direction of the DC motor which is located at the receiver side.